'Work not as usual': work and industrial relations in a post-COVID world. (2nd January 2023) - Dabaja, Isabella; Dinale, Daniel; Gulesserian, Lisa; Wright, Chris F
ABSTRACT: This article introduces the Labour & Industry special issue on 'work not as usual', following the theme of the 2022 AIRAANZ Conference. In introducing the articles published in the special issue, it examines key themes regarding how work and industrial relations are changing in unusual ways. These relate to the impacts of COVID-19; how work and industrial relations are shifting in the public sector and in the care economy; and how workers and organisations are responding to changes at work through voice, control and resistance. Analysis of these developments in the articles published in this special issue suggest that organisations and labour markets will continue to be defined by 'work not as usual' into the foreseeable future.